The contending futures of UN peacekeeping - Corine van Emmerik; Peter Albrecht (Danish Institute for International Studies (DIIS), 2025)
This paper examines the contending futures of United Nations (UN) peacekeeping through an analysis of key UN publications and interviews conducted in New York in 2024. At a time when peacekeeping faces multiple challenges - including a crisis of trust, diminished legitimacy, and a deadlocked Security Council - the study traces how visions of peacekeeping's future reflect the organisation's decision-making processes, institutional constraints, and political interests. By analysing documents and interviews with UN officials and diplomats, the paper identifies three emergent categories: broadened futures emphasising flexibility and integration; suspended and anticipated futures awaiting catalytic moments; and retroactive futures advocating return to core principles. Rather than offering prescriptive recommendations, the paper argues that peacekeeping's chronic challenges are inherently unsolvable and must be continuously navigated. The analysis concludes that peacekeeping's future lies not in fixed forms but in functional flexibility, reflecting broader tensions within the UN system itself.
Keywords: 330